(untitled) (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2021)
In his marriage with Tambangraras, Sheikh Amongraga made several demands based on Islamic teachings. The demands were written in Serat Centhini chapter 6 which involved the demands for holding the marriage in an ordinary way (inviting a small number of guests to avoid being arrogant (takabbur), eliminating occult practices (klenik) which led to the sin of idolatry (shirk), getting rid of the loro blonyo statue, allowing Tambangraras to bring a lawsuit if Sheikh Amongraga did not fulfil his responsibility within a certain period, teaching the Quran which was used as a dowry as it was considered as a debt, and allowing Niken Tambangraras to get married when Sheikh Amongraga died during his odyssey. The data of this study was derived from Serat Centhini 6 and Serat Centhini 7. The data was analyzed by using an analytical descriptive method based on textual objective data (an objective literary study). The conclusion drawn from this study is that the demands made by Sheikh Amongraga to his future parents-in-law and Niken Tambangraras in their marriage were based on Islamic values that he held.